True biz : a novel [large type] - Nović, Sara, 1987- (Thorndike Press large print core series., 2022)
"True biz? The students at the River Valley School for the Deaf just want to hook up, pass their history finals, and have politicians, doctors, and their parents stop telling them what to do with their bodies. This revelatory novel plunges readers into the halls of a residential school for the deaf, where they'll meet Charlie, a rebellious transfer student who's never met another deaf person before; Austin, the school's golden boy, whose world is rocked when his baby sister is born hearing; and February, the hearing headmistress, a CODA (child of deaf adult(s)) who is fighting to keep her school open and her marriage intact, but might not be able to do both. As a series of crises both personal and political threaten to unravel each of them, Charlie, Austin, and February find their lives inextricable from one another--and changed forever. This is a story of sign language and lip-reading, disability and civil rights, isolation and injustice, first love and loss, and, above all, great persistence, daring, and joy. Absorbing and assured, idiosyncratic and relatable, this is an unforgettable journey into the Deaf community and a universal celebration of human connection"--